Effects of Temperature and Strain Rate on Mechanical Behaviour of Laser Rapid Forming Ti-6Al-4V Alloy. (September 2020) - Xiang, Wenli; Shu, Xinzhu; Sun, Kun
Abstract: Using the electronic universal test machine, the high temperature split Hopkinson bar and the gleeble-1500 thermal simulator, the room temperature quasi-static compression experiment, room temperature dynamic compression experiment, high temperature dynamic compression experiment and the high temperature quasi-static compression experiment on corresponding cylindrical samples of Laser Rapid Forming Ti-6Al-4V(LRF TC4) titanium alloy have been conducted, respectively. And effects of the temperature and strain rate on mechanical behavior of LRF TC4 alloy have been investigated. It is showed that, whether quasi-static compression or high strain rate compression, the strength of LRF TC4 decreases and the plasticity increases at the high temperature. Under the high temperature quasi-static compression, LRF TC4 still has the strain strengthening effects at 400°C, the flow stress changes steadily in the stage of the plastic deformation at 500°C and the strength of LRF TC4 dropped drastically when the temperature goes beyond 500°C. Under the high temperature and high strain rate, the flow stress changes steadily in the plastic deformation stage due to dual function of both strain rate strengthening and temperature softening and adiabatic temperature rise within the sample reduced with the increase of the deforming temperature. Under the coupling function of high temperature and high strain rate, the effect of strain-rate strengthening is weaker than the effect of temperature softening.